The Accounting Profession in the Context of Globalisation - Dorel MATEȘ; Roxana Mirella IRIMUȘ (CECCAR Business Review, 2021)

(untitled)
This paper presents the globalisation factors that have the biggest impact on the accountancy profession. The International Financial Reporting Standards are the core of accounting globalisation, providing transparency and comparability all over the world. Concerning globalisation, there is a need to discuss the increasing development of competition and technology that also have a major impact on accountancy.